Role of complement receptor 1 (CR1; CD35) on epithelial cells: A model for understanding complement-mediated damage in the kidney. Issue 2 (October 2015) - Java, Anuja; Liszewski, M. Kathryn; Hourcade, Dennis E.; Zhang, Fan; Atkinson, John P.
Highlights: CR1 is an exceptionally potent regulator of the alternative pathway. Inhibition of complement activation is mediated via decay accelerating activity. Deposited C4b and C3b are processed by cofactor activity with a t ½ of ∼ 30 min. CR1 functions as an intrinsic but not an extrinsic regulator. CR1 stably and efficiently binds C3b/C4b opsonized immune complexes. Abstract: The regulators of complement activation gene cluster encodes a group of proteins that have evolved to control the amplification of complement at the critical step of C3 activation. Complement receptor 1 (CR1) is the most versatile of these inhibitors with both receptor and regulatory functions. While expressed on most peripheral blood cells, the only epithelial site of expression in the kidney is by the podocyte. Its expression by this cell population has aroused considerable speculation as to its biologic function in view of many complement-mediated renal diseases. The goal of this investigation was to assess the role of CR1 on epithelial cells. To this end, we utilized a Chinese hamster ovary cell model system. Among our findings, CR1 reduced C3b deposition by ∼ 80% during classical pathway activation; however, it was an even more potent regulator (>95% reduction in C3b deposition) of the alternative pathway. This inhibition was primarily mediated by decay accelerating activity. The deposited C4b and C3b were progressively cleaved with a t ½ of ∼ 30 min to C4d and C3d, respectively, by CR1-dependent cofactor activity. CR1 functioned intrinsically (i.e, worked only on the cell on which it was expressed). Moreover, CR1 efficiently and stably bound but didn't internalize C4b/C3b opsonized immune complexes. Our studies underscore the potential importance of CR1 on an epithelial cell population as both an intrinsic complement regulator and an immune adherence receptor. These results provide a framework for understanding how loss of CR1 expression on podocytes may contribute to complement-mediated damage in the kidney.